2001
DOI: 10.1046/j.1365-2664.2001.00625.x
|View full text |Cite
|
Sign up to set email alerts
|

Predation on livestock by an expanding reintroduced lynx population: long‐term trend and spatial variability

Abstract: Summary In recent decades, the Eurasian lynx Lynx lynx has recolonized former habitat, bringing it into potential conflict with livestock. We studied the spatial and temporal distribution of lynx attacks on sheep in the French Jura between 1984 and 1998, during and after its population expansion. We estimated the local and regional impact of lynx predation on livestock. The number of attacks increased from three in 1984 to 188 in 1989, concurrently with the colonization of the main sheep range by lynx. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
107
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(111 citation statements)
references
References 34 publications
3
107
1
Order By: Relevance
“…For example, snow leopard (Uncia uncia) in the Himalayas (Bagchi & Mishra, 2006) and wolf (Canis lupus) in Southern Europe (Meriggi & Lobari, 1996) showed an inverse relationship between the abundance and richness of wild prey and occurrence or frequency of attacks to domestic ungulates. On the other hand, European lynx (Lynx lynx) in Norway (Odden, Herfindal, Linnell, & Andersen, 2008) and France (Stahl, Vandel, Herrenschmidt, & Migot, 2001;Stahl et al, 2002) showed that attacks on sheep match with areas with high abundance of roe deer (Capreolus capreolus). Focusing on jaguar and puma, Polisar et al (2003) and Cavalcanti and Gese (2010) showed that these big cats selected wild prey even when cattle were available at the Llanos of Venezuela and Pantanal of Brazil, respectively.…”
mentioning
confidence: 99%
“…For example, snow leopard (Uncia uncia) in the Himalayas (Bagchi & Mishra, 2006) and wolf (Canis lupus) in Southern Europe (Meriggi & Lobari, 1996) showed an inverse relationship between the abundance and richness of wild prey and occurrence or frequency of attacks to domestic ungulates. On the other hand, European lynx (Lynx lynx) in Norway (Odden, Herfindal, Linnell, & Andersen, 2008) and France (Stahl, Vandel, Herrenschmidt, & Migot, 2001;Stahl et al, 2002) showed that attacks on sheep match with areas with high abundance of roe deer (Capreolus capreolus). Focusing on jaguar and puma, Polisar et al (2003) and Cavalcanti and Gese (2010) showed that these big cats selected wild prey even when cattle were available at the Llanos of Venezuela and Pantanal of Brazil, respectively.…”
mentioning
confidence: 99%
“…Given that these individuals represented only 2 of 49 Striped Skunks captured and were only captured 2 and 3 times, respectively, in the present study and that Vickery et al (1992) reported predation by Striped Skunks on nests of birds was not targeted, these results do not corroborate the "problem-individual" paradigm. Additionally, in comparison with larger mammalian predators, this paradigm has been associated, generally, with much higher levels of predation and by greater numbers of individuals repeatedly involved in taking prey (Claar et al 1986;Stander 1990;Ross et al 1997;Sacks et al 1999;Stahl et al 2001). Scalet et al (1996) pointed out that predator-prey interactions influence both prey and predator populations.…”
Section: Discussionmentioning
confidence: 99%
“…They refer to the phenomena as the "problem-individual" paradigm. Although this paradigm appears to fit some larger carnivores (Rabinowitz 1986;Ross et al 1997;Sacks et al 1999;Stahl et al 2001), the hypothesis rarely has been tested (Linnell et al 1999). Presently, the existence of individuals or a demographic group within mid-sized mammalian predators that prey upon a disproportionate number of nests of ground-nesting birds is unknown.…”
mentioning
confidence: 99%
“…Although the underlying assumption of the problem-individual paradigm had been little tested (Linnell et al 1999), more recent studies, on a number of species, have shown that a small proportion of individuals in the predator population can be responsible for the majority of predation events (Stahl et al 2001;Marquiss et al 2003a;Rosas-Rosas et al 2008). The observation that only a small proportion of radio-tagged buzzards associated with pheasant pens (Kenward et al 2001), together with the anecdotal reporting that the removal of two buzzards from a poultry farm was followed by a cessation of predation, gives some support to this idea.…”
Section: Invasive Techniquesmentioning
confidence: 99%
“…More recently, however, at a poultry farm, the licensed removal of one adult buzzard was followed by a cessation in predation events that had previously persisted for around 18 months (Natural England pers comm). For a number of other predator species, studies have shown that predation events on livestock can be unevenly distributed across the predator population, with a small number of individuals responsible for a significant majority of total kills (Eurasian lynx Lynx lynx, Stahl et al 2001; white-tailed eagle, Marquiss et al 2003a; jaguar Panther onca, RosasRosas et al 2008).…”
Section: Extent and Magnitude Of Impactsmentioning
confidence: 99%